(untitled) (Comparative Professional Pedagogy, 2021)
The article differentiates the categories of professional competence, communicative competence and foreign language communicative competence on the basis of Ukrainian and foreign sources. According to the findings, professional competence depends on the specificity of organizational goals and professional functions. Communicative competence is described as the ability to engage into communication with the individual as well as within a group while choosing various tools of communication and ensuring transferring and understanding of the information. Foreign language communicative competence of future military officers is described as important instrument to carry out their professional duties by means of foreign language. The process of formation of foreign language communicative research at the higher military educational establishments has its own characteristics. First of all, the content of foreign language professional training should be related to professional activities and outline the functionality and social role of military officers. Also, effective syllabus and curricula should be objectively approximated to cadets’ and/or officers’ needs. The assessment of English language proficiency of the military officers is carried out in accordance with the NATO Standardization Agreement. The article analyses Language proficiency levels and didactic activities of those who study. They include receptive (reading and listening) and productive (speaking and writing) activities. The teacher’s professionalism plays the significant role in the learning process but the analysis of foreign experience provides the description of special methodology oriented towards improvement of four language skills (listening, reading, speaking, and writing) at the higher military educational establishment. Additionally, the article outlines the guidelines to improve foreign language training designed according to the STANAG 6001 and to reach level 2 by future military officers in Ukrainian military educational establishments.